Expression profiles of growth-related genes in two Nile tilapia strains and their crossbred provide insights into introgressive breeding effects - Herkenhoff, M. E. [UNESP]; Ribeiro, A. O. [UNESP]; Costa, J. M. [UNESP]; Oliveira, A. C. [UNESP]; Dias, M. A.D.; Reis Neto, R. V. [UNESP]; Hilsdorf, A. W.S.; Pinhal, D. [UNESP] (Wiley, 2020)
The Nile tilapia (Oreochromis niloticus) is a prominent farmed fish in aquaculture worldwide. Crossbreeding has recently been carried out between the Red-Stirling and the wt Chitralada strains of Nile tilapia, producing a heterotic hybrid (7/8 Chitralada and 1/8 Red-Stirling) that combines the superior growth performance of the Chitralada with the reddish coloration of the Red-Stirling strain. While classical selective breeding and crossbreeding strategies are well known, the molecular mechanisms underlying the phenotypic expression of economically advantageous traits in tilapia remain largely unknown. Molecular investigations have shown that variable expression of growth hormone (gh), insulin-like growth factors (igf1 and 2) and somatolactin (smtla) – components of the growth hormone/insulin-like growth factor (GH/IGF) axis – and myostatin (mstn) genes can affect traits of economic relevance in farmed animals. The aim of this study was to assess and compare the gene expression signature among Chitralada, Red-Stirling and their backcross hybrid in order to gain insights into the effects of introgressive breeding in modulation of the GH/IGF axis. Gene expression analyses in distinct tissues showed that most genes of the GH/IGF axis were up-regulated and mstn was down-regulated in backcross animals in comparison with Red-Stirling and Chitralada animals. These gene expression profiles revealed that backcross animals displayed a distinctive expression signature, which attests to the effectiveness of the introgressive breeding technique. Our findings also suggest that the GH/IGF axis and mstn genes might be candidate markers for fish performance and prove useful within genetic improvement programs aimed at the production of superior-quality tilapia strains using introgressive breeding.
Keywords: growth hormone; insulin-like growth factor; introgressive hybridization; myostatin; somatolactin